Assessment of interobserver variability in Gleason grading for prostate carcinoma - Cinar, Ilkay (Northern Clinics of Istanbul, 2025)
The Gleason Score is the most widely used grading system for prostate adenocarcinoma and it is the strongest predictor of the patient's clinical outcome similar to other grading systems, and plays a key role in determining the most effective treatment strategy for the patient. The Gleason scoring system is subject to both intraobserver and interobserver variability. This study aims to assess the interobserver agreement for prostate adenocarcinoma within the Gleason grading system at our center, as well as identify contributing factors. A total of 119 cases diagnosed with prostatic adenocarcinoma at Giresun Training and Research Hospital were included in the study. Tissue samples from the cases had been subjected to routine laboratory procedures; three-micron sections were obtained from formalin-fixed paraffin blocks and stained H&E. Statistical investigation was conducted on the agreement between Gleason pattern, Gleason sum score, and grade group data among three observers. In the evaluation, interobserver agreement was found to be minimal (Gleason pattern k=0.285, total Gleason sum score k=0.309, Grade group k=0.313). The assessment indicated higher agreement in determining low grade compared to high grade, with a decrease in interobserver agreement as the grade increased. Moreover, interobserver agreement demonstrated an increase over the years (p<0.001). The findings underscore the ongoing inadequacy of interobserver agreement in the Gleason scoring system. Improvement suggestions involve conducting studies to ascertain in-clinic interobserver agreement enhancing training, facilitating information sharing, and employing accessible and easily applicable artificial intelligence-supported programs.